Assessment of liver stiffness and steatosis in patients with intestinal failure: a cross-sectional study - Muhic, Ena; Naimi, Rahim Mohammad; Brandt, Christopher Filtenborg; Andersen, Thomas Lund; Johannesen, Helle Hjorth; Jeppesen, Palle Bekker (Frontiers in Nutrition, 2025)
IntroductionIntestinal failure-associated liver disease is a potentially life-threatening complication in patients with intestinal failure (IF) receiving home parenteral support (HPS). The aim of this study was to evaluate liver stiffness and steatosis non-invasively in adult patients with IF receiving long-term HPS.MethodsPatients with IF on a stable HPS prescription (≥4 days/week for ≥10 weeks) were included in this cross-sectional study. Liver stiffness measurements (LSMs) were assessed by transient elastography, and steatosis by MRI-proton density fat fraction (MRI-PDFF). Blood samples were analyzed for liver function. Data were compared to sex- and age-matched controls.ResultsA total of 33 patients (median age, 57 years; BMI, 23 kg/m2) and 14 controls (median age, 58 years; BMI, 24 kg/m2) were examined. Patients had higher LSMs compared to controls (5.6 kPa vs. 4.3 kPa; p = 0.0079). Elevated LSMs (>7 kPa) were seen in 37% of patients vs. 0% in controls (p = 0.0085). LSMs were associated with HPS energy (p = 0.026) and lipid content (p = 0.029). Median MRI-PDFF was 1.8% in patients and 1.5% in controls (p = 0.43). Nineteen percent of patients exhibited elevated MRI-PDFF (≥8%) vs. 7% in controls (p = 0.41). Alkaline phosphatase and gamma-glutamyltransferase levels >1.5x the ULN were observed in 21 and 45% of patients, respectively. Overall, these results indicate that in this adult IF population, elevated LSMs and a cholestatic pattern in liver enzymes were more prevalent than steatosis as assessed by MRI-PDFF. Patients at risk of increased liver stiffness appeared to have severe IF as indicated by high HPS energy and lipid requirements.